Gastric preconditioning in advance of esophageal resection-systematic review and meta-analysis - Heger, Patrick; Blank, Susanne; Diener, Markus K.; Ulrich, Alexis; Schmidt, Thomas; Büchler, Markus W.; Mihaljevic, André Leopold (Journal of gastrointestinal surgery, 2017)
Background Anastomotic leakage is one of the most severe complications following esophageal resection. Among other strategies, gastric ischemic preconditioning has been proposed to improve anastomotic integrity. The aim of this systematic review is to investigate whether gastric preconditioning has influence on peri- or postoperative outcomes after esophageal resection. Methods A systematic literature search was performed to identify studies comparing gastric preconditioning with nonpreconditioned patients for any indication of esophageal resection. Random-effects meta-analyses were conducted for main outcomes. Results Gastric preconditioning did not reduce anastomotic leakages (OR 0.76; 95%-CI 0.51 to 1.13; p = 0.18), anastomotic strictures (OR 1.10; 95%-CI 0.58 to 2.10; p = 0.76;), major complications (OR 1.14; 95%-CI 0.60 to 2.14; p = 0.69), or inhospital mortality (OR 0.62; 95%-CI 0.28 to 1.40; p = 0.25). However, preconditioning reduced the rate of severe leaks requiring reoperation (OR 0.20; 95%-CI 0.08 to 0.53; p = 0.001). Increasing the period between preconditioning and esophageal resection over 2 weeks did not reduce anastomotic leakage compared to shorter waiting times (OR 0.65; 95%-CI 0.38 to 1.13; p = 0.13). Conclusion With current evidence, gastric preconditioning does not seem to reduce overall rates of anastomotic leakage after esophageal resection but seems to reduce severity of leakages.
Published 24 April 2017
Gesehen am 24.10.2018